My PhD in English literature at Portsmouth - Hasan, Md. Mahmudul (2019)
Since I completed my PhD at Portsmouth, I have undertaken a number of meaningful research projects and published many works with presses in the east and west. Had Bronwen and Alex been lenient with me regarding the quality of my work and had I navigated through my doctoral journey with relative ease, perhaps my PhD thesis would have remained the main landmark of my academic career with little to no further research.